Nalar Filsafat dan Teologi Islam: Upaya Membentengi Pengetahuan dan Teologi Islam - JABIR, Muhammad Abed (IRCiSoD, 2003)
Nalar Filsafat dan Teologi Islam: Upaya Membentengi Pengetahuan dan Teologi Islam